Peningkatan produksi petani Jamur Tiram dengan teknik kultur di Kota Medan - Yurnaliza Yurnaliza; Liana Dwi Sri Hastuti; Riyanto Sinaga; Adrian Hartanto; Wita E Tarigan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Oyster mushrooms are one of the commodities that people are interested in to meet the needs of healthy and nutritious foods, where the demand of this fungus increases every year. In the city of Medan, oyster mushroom cultivation has begun to develop in the home industry, small to medium scale industries, but in fact it has not yet fulfilled the market demand. The low production of oyster mushrooms caused by the low knowledge of the farmer in preparation of the seed, either F-0, F-1, F-2 or F-3 and ultimately fail in baglog preparation as the final media stage for oyster mushroom production. In the seedlings and backlogs manufacturer should follow the technical culture standard preparation of seedling. Socialization has been carried out by Tim ABDIMAS with the demonstration and introducing culture and sterilization technique using saving energy autoclave, efficient in use for the mushroom farmers and expected after the program the farmers can be confident and become independent in spawn or seedling producing by themselves. The use of autoclave is very effective and significant in reducing the number of contaminated seedlings, as seen in the graph which is also presented in this paper. Knowledge of making mushroom flour with a simple method with low cost in contemporary and hygienic packaging ready to be marketed as a basic ingredient in food processed products or as an ingredient in traditional medicine is also provided.